NURSING CARE FOR CLIENTS PNEUMONIA WITH NURSING PROBLEMS OF AIRWAY CLEANING IS INEFFECTIVE IN THE GATUTKACA ROOM AT THE JOMBANG GENERAL HOSPITAL - Sely Delta Surya Ningsih; Achmad Wahdi; Tiara Fatma Pratiwi; Arif Wijaya; Faishol Roni (Universitas STRADA Indonesia, 2023)
Background : Nursing care of pneumonia clients with ineffective airway clearance nursing problems using chest physiotherapy. Methods : The research design used a case study of 2 clients with pneumonia with nursing problems. Ineffective airway clearance on the first day, nursing care was carried out for 3 days in a row using an intervention, namely chest physiotherapy. Results : Research shows the problem of ineffective airway clearance with chest physiotherapy, the problem is resolved in reducing shortness of breath. Analysis : The purpose of this study was to carry out nursing care in pneumonia patients with nursing problems ineffective airway clearance using chest physiotherapy. Conclusion : Chest physiotherapy is used as an adjunct therapy to prevent non-pharmacological increases in shortness of breath in pneumonia patients.